Effect of Taobao village certification on agricultural fertilizers and pesticides usage in China - Huayue Guo; Chao Wang (Sustainable Futures)
Employing the Taobao village certification (TVC) as an exogenous policy shock and leveraging balanced panel data at the county level from 2007 to 2021, our multi-period Difference-in-Differences (DID) analysis reveals that the TVC reduces agricultural fertilizers and pesticides usage by 5 % to 10 %. This environmental benefit primarily stems from facilitating labor transfer and advocating for environmentally sustainable agriculture. Moreover, a more pronounced pollution reduction effect is observed in counties with higher marketisation level and major grain-producing areas. Our paper holds significant practical implications for rural environmental governance and potentially for other agricultural powerhouses where e-commerce is flourishing.